Marketing Strategy Analysis Of Back To Back Financing Products In Attracting Customers' Interest In Bank Muamalat Kcu Padangsidimpuan - Saleh, Idris; Zahra, Rizky Amelia; Afifah, Nurul (Journal of Islamic Financial Technology, 2022)
This research is motivated by a lot of competition between banks and other financial institutions in attracting customers so that it can increase the number of customers. And one way is to implement a 7 P marketing strategy, namely Product, Price, Place, Promotion, People, Process , and Physical Evidence . The purpose of this study was to determine the marketing strategy of back to back financing products in an effort to attract customers' interest at Bank Muamalat KCU Padangsidimpuan . This research is a type of field research (Field Research). with a qualitative approach. This study uses triangulation techniques in the process of checking the validity of the data. The results of this study indicate that the marketing strategy of back to back financing products carried out by Bank Muamalat KCU Padangsidimpuan is an effective strategy applied, especially promotion because it can increase public knowledge about the product.Keywords: Customers , Interests , Financing , Strategy